THE ESOPHAGUS IN RADIOLOGIC PROBLEMS - Arbuckle, Robert K. (1954)
Examination of the esophagus must go considerably beyond observation of “a barium swallow”; it must include a thorough study of the hypopharynx, the cervical esophagus and the thoracic esophagus. Dysphagia, which is almost always the presenting complaint, may be due to a number of lesions originating outside the esophagus and thus cause no sign of mucous membrane destruction or of filling defect.